Health promotion in workplaces with a large share of older employees. The situation in Poland - Eliza Goszczyńska (Nofer Institute of Occupational Medicine, 2020)
Background In the nearest decades, the ageing process in Poland is likely to intensify, leading to the shrinking of workforce. An increase in the share of older employees having worse health may deteriorate certain worksite parameters (i.e., resulting in increased sickness absence). Enterprises may face such challenges by promoting employees' health. The paper aims at answering the question whether enterprises with a large share of older employees (aged ≥55) are more aware of the ageing process and more interested in promoting health of their personnel than organizations hiring mostly younger employees. Material and Methods The survey covered 926 companies selected from a representative sample of 1000 enterprises in Poland hiring ≥50 employees, which were aware of the share of employees aged ≥55 among their staff. The analyses were conducted in 4 groups of enterprises, depending on the share of ageing employees, i.e., enterprises not hiring such employees (N = 43), and enterprises with ageing employees accounting for less than one-fourth (N = 493), from one-fourth to a half (N = 335), or more than a half (N = 55) of their personnel. Standardized computer-assisted personal interviews (CAPI) with delegates of the boards were held in October-November 2017. Results Organizations with the majority of older employees have the greatest awareness of population ageing, its consequences and the deepest sense of investing in employees' health. They are also more willing than worksites not employing people aged ≥ 55 to analyze the health needs of their personnel of different age and to implement health promotion measures. The problem is that they are less interested in the evaluation of such activities. Conclusions Although enterprises employing mostly people aged ≥ 55 are the most aware of population ageing and likely to implement many health promotion measures, many of them appear to neglect this demographic process. Many companies promoting employees' health do so for other reasons than to diminish the consequences of population ageing. Thus, employers should be made aware of the inevitability of ageing and health promotion as a tool in coping with the outcomes of that process. They should also be encouraged to evaluate their health promotion measures. Med Pr. 2020;71(2):153-76